Ovotesticular disorder of sex development in a tertiary care center in North India: A single-center analysis over a 5-year period - Sarita Chowdhary; Maneesha Upadhayaya; Gunjan Rai; Manpreet Kaur; Nitish Kumar Singh; Kanika Sharma; Ritesh Yadav; Bitan Naik; Shiv Prasad Sharma; Royana Singh (Wolters Kluwer Medknow Publications, 2023)
Background: Disorders of sexual development (DSD) encompass a group of congenital conditions characterized by diverse genotypic and phenotypic variations. Ovotesticular (OT) DSD is a distinctive subtype within this spectrum. Among the array of DSD, OT-DSD stands as one of the most infrequent anomalies, with reported prevalence rates as scarce as 1 in 83,000. This study aims to elucidate the clinical, hormonal, cytogenetic, surgical, and histopathological characteristics of OT disorder of sex development (OT-DSD) within a tertiary center in North India. Methodology: A retrospective analysis was conducted, involving a comprehensive review of records pertaining to OT-DSD patients from the years 2018 to 2022, all of whom were incorporated into the study. Results: The mean age of presentation in this study was 10 years, spanning from 6 to 15 years. Predominantly, the affected individuals were male, with a solitary patient representing the female category. Clinical manifestations displayed a spectrum encompassing genital ambiguity, inguinal swelling, and primary amenorrhea. The karyotypes observed were 46,XX in four patients and 46,XY in one patient. A holistic assessment, inclusive of clinical evaluation, hormonal assays, pelvic ultrasonography, and surgical intervention when necessary, was administered to all patients. Among these cases, three patients were reared as males, their gender assignment driven by external genital appearance and sociocultural influences. Notably, none of the patients manifested gonadal tumors during the course of the study. Conclusion: In cases of ambiguous genitalia, the consideration of OT-DSD should be integral to the differential diagnosis, underscoring the significance of heightened clinical awareness and informed decision-making.